Relationship between Work Motivation and Organizational Culture in Enhancing Professional Attitudes of Pakuan University Lecturers - Yudhie Suchyadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
The objectives of this study was to examine the relationship between work motivation, organizational culture toward lecturers professional attitudes. The research was conducted at study program of Pakuan University. The applied research methods are survey method and data analysis technique using the correlation and simple linier regression as well as correlation and multiple linier regression statistical. This research can be classified into correlation research which consist of two independent variables namely work motivation, organizational culture and one dependent variable namely lecturers professional attitudes. This research involved samples of 166 permanent lecturers which were selected by proportional random sampling. Meanwhile, the hypothesis test is conducted on 0.05 significance level. Results emerged that there is a positive relationship between all variables tested in the study. First, there is a positive and significant correlation between the work motivation with the lecturers professional attitudes with regression equation of ?= -1.79 + 1,04X1 and correlation coefficient ry1 = 0.997. The contribution of the work motivation toward the lecturers professional attitudes is 99,7%. Second, there is a positive and significant between correlation the organizational culture with the lecturers professional attitudes with regression equation of ?= -3,06 + 1,02 X2 and correlation coefficient ry2 = 0.997. The contribution of the organizational culture toward the lecturers professional attitudes is 99,7%. Third, there is a positive and significant correlation between the work motivation with organizational culture combined with the lecturers professional attitudes with regression equation of ?= -2,634 + 0,528X1 + 0,505X2 and correlation coefficient ry12 = 0,998. The contribution of the work motivation and organizational culture toward the lecturers professional attitudes is 99,8%. Based on the results above it can be concluded that the lecturers professional attitudes can be improved through a high working motivation and the organizational culture